Odpowiedzi

  • Użytkownik Zadane
2009-08-03T12:55:07+02:00
Y=ax+b
a)
A=(0,-1)
x=0, y=-1
-1=a*0+b
-1=b
b=-1

B=(2,5)
x=2, y=5
5=a*2+b
5=2a+(-1)
5=2a-1
5+1=2a
2a=6/:2
a=3

y=3x-1


b)
y=ax+b
A=(-2,3)
x=-2, y=3
3=a*(-2)+b
3=-2a+b

B=(1,9)
x=1, y=9
9=a*1+b
9=a+b

uład równań
-2a+b=3
a+b=9/*2

-2a+b=3
+ 2a+2b=18

3b=21/:3
b=7

2a+2*7=18
2a=18-14
2a=4/:2
a=2

y=2x+7

c)
y=ax+b
A=(-1,5)
x=-1, y=5
5=a*(-1)+b
5=-a+b

B=(1,-3)
x=1, y=-3
-3=a*1+b
-3=a+b

układ równan

-a+b=5
+ a+b=-3

2b=2/:2
b=1

a+1=-3
a=-4

y=-4x+1